Sustainable Business Performance In Tourism Smes: The Role Of Entrepreneurial Competency, Sustainable Competitive Advantage, And Ecosystem Support - Reagan Brian; Diena M Lemy; Henricus Kurniawan Elang Kusumo (Journal of Business on Hospitality and Tourism, 2026)
Tourism SMEs in developing economies face unique pressures: resource constraints, institutional gaps, and growing demands for environmental and social accountability that larger firms can absorb but small operators must actively navigate. This study examines how entrepreneurial competency drives sustainable business performance in tourism SMEs, using competitive sustainability as a mediating mechanism and entrepreneurial ecosystem support as a moderating condition. Drawing on the Resource-Based View and Institutional Theory, a moderated mediation model was tested on survey data from 230 tourism SME owners and managers, analyzed via PLS-SEM. Entrepreneurial competency positively influences both competitive sustainability and sustainable business performance, while competitive sustainability partially mediates that relationship. Ecosystem support significantly strengthens these effects, amplifying the capacity of entrepreneurs to convert internal capabilities into sustained outcomes. The findings offer an integrated framework that positions sustainable performance as the product of aligned entrepreneurial capability, competitive strategy, and ecosystem conditions.